Efficacy of Whole-Blood Exchange Transfusion in Refractory Severe Autoimmune Haemolytic Anaemia Secondary to Systemic Lupus Erythematosus: A Real-World Observational Retrospective Study - Jiang, Ying; Zhao, Hong Jun; Luo, Hui; Li, Bi Juan; Zhang, Zhi Min; Zhao, Li Dan; Zuo, Xiao Xia (Frontiers in Immunology, 2022)
Background Severe autoimmune haemolytic anaemia (AIHA) in systemic lupus erythematosus (SLE) patients could be life-threatening and formidable, especially in those non-responsive to glucocorticoid (GC) and immunosuppressant (ISA). Whole-blood exchange transfusion (WBE), with plasma exchange and pathogenic cell removal as well as healthy red blood cell transfusion could be beneficial. The objective of this study was to investigate the efficacy and safety of WBE in combination with GC/ISA. Methods In this retrospective study, the clinical data of 22 refractory severe SLE-AIHA inpatients between February 2016 and February 2021 were collected and analysed, among whom 14 patients had received WBE and were compared with those treated with typical second line therapy of intravenous immunoglobulin and/or rituximab (IVIG/RTX). Results Among the 22 refractory severe SLE-AIHA patients, eight patients received IVIG and/or RTX without WBE (group 1, IVIG/RTX, n=8), seven patients were given WBE without IVIG/RTX (group 2, WBE alone, n=7), and seven patients who failed initial IVIG/RTX therapy were given sequential WBE therapy (group 3 IVIG/RTX→WBE, n=7). Fourteen patients had accepted WBE treatment regardless of prior IVIG/RTX usage (group 2+3, WBE ± IVIG/RTX, n=14). On day 1, day 3, day 5 and day 7 after corresponding therapies, patients of group 2, group 3 and group 2+3 showed significant higher levels of Hb than patients of group 1. Compared with patients of group 1, patients of group 2, group 3 and group 2+3 took less time to reach and maintain Hb≥60 g/L from baseline. Group 2 and group 2+3 had consumed lower dose of GC than group 1 to reach and maintain Hb≥60 g/L from baseline. Group 1 experienced longer hospital stay than group 2, and group 3 cost more in hospitalization than group 1 and group 2. Hbmin < 40 g/L may be a key indicative factor for initiating WBE remedy therapy as IVIG/RTX may not be effective enough in 48-72h in those refractory severe SLE-AIHA patients. No severe adverse effects had been observed in WBE group. Conclusions WBE could be a safe and beneficial alternative therapy in refractory severe SLE-AIHA.